Pengaruh Inovasi Produk dan Literasi Keuangan Terhadap Kinerja Keuangan: Peran Komitmen Pemilik Sebagai Variabel Moderasi: Studi Kasus pada UMKM di Coastal Area Tanjung Balai Karimun - Azura Novi; Muammar Khaddafi; Nolla Puspita (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this study is to examine: 1) The impact of Product Innovation on Financial Performance, 2) The influence of Financial Literacy on Financial Performance, 3) The effect of Product Innovation on Financial Performance moderated by the Role of Owner Commitment, 4) The effect of Financial Literacy on Financial Performance moderated by the Role of Owner Commitment, and 5) The impact of the Role of Owner Commitment on Financial Performance. This research is a descriptive quantitative study using primary data, with a sample of 95 respondents randomly selected from SMEs in the Coastal Area. The data was analyzed using Structural Equation Modeling (SEM) with the help of SmartPLS 3.0 software. The results of the analysis indicate that: 1) Product innovation has a significant impact on financial performance, with a t-statistic value of 2.166  >1,96, 2) Financial literacy significantly affects financial performance, with a t-statistic value of 4.401 >1,963) Product innovation does not significantly affect financial performance when moderated by the role of owner commitment, with a t-statistic value of 1.293 (less than >1,96), 4) Financial literacy does not significantly affect financial performance when moderated by the role of owner commitment, with a t-statistic value of 1.272 (less than >1,96) and 5) The role of owner commitment significantly influences financial performance, with a t-statistic value of 4.387 >1,96.